Prognosis and management of polymyalgia rheumatica - Samara, Diana (Universa Medicina, 2011)
Polymyalgia rheumatica (PMR) is commonly found in Northern Europe and in persons of Scandinavian extraction in the US, with an annual incidence of around 50 per 100,000 population over 50 years of age, in whom it should be           considered in the differential diagnosis of musculoskeletal disorders. The     disorder is twice more common in women than in men. PMR is closely related to giant cell arteritis and both disorders are considered to have a common    pathogenesis, associated with genetic and environmental factors (viral and   bacterial infections). There is no gold diagnostic standard for PMR and the diagnosis rests on a high index of suspicion in persons older than 50 years with musculoskeletal symptoms. As an aid in diagnosis, several sets of diagnostic criteria have been used, usually related to age at onset, duration, symptoms, inflammatory markers, and response to corticosteroids. Patients with PMR   usually present with acute onset of stiffness and pain in the shoulder and pelvic musculature, which may be accompanied by fever, malaise, and weight loss. The symptoms of PMR seem to be related to synovitis of proximal joints and extra-articular synovial structures. PMR may occur as an isolated syndrome or accompany other diseases, mainly giant cell arteritis. It usually responds quickly to once-daily, low-dose prednisone, but some patients require treatment for  several years. Monitoring for corticosteroid-associated side effects such as   osteoporosis and diabetes, as well as for relapses and flare-ups, is key to chronic management.